Mediating Role of Attitudes to Enhance the Creativity Disposition towards Entrepreneurial Intention - Anjum, Temoor (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research was to examine the mediating role of attitude to enhance the creativity disposition towards entrepreneurial intention. The population of this research comprised university students in Pakistan. 313 students were selected as the sample from the seven universities. The stratified random sampling technique was executed. Cross-sectional and quantitative research design based on the survey method was used for this research. A questionnaire comprised of three sections was used for data collection. Smart PLS-3 was used to assess the hypothesis of this study. The results of this study highlighted the significance of the mediating role of attitudes to enhance the creativity disposition towards entrepreneurial intention while attitudes and entrepreneurial intention have a significant correlation between each other.